Representaciones sociales sobre los adultos mayores en los informativos de televisión de Latacunga. - Caisaguano Yugcha, Karen Alexandra (2018)
This research project is directly related to the problems surrounding the creation and diffusion of information content, in which older adults are involved, referring to them through inappropriate terms or social representations, in addition to forget the means of communication towards long-lived people when the festive dates are over, for which the study focuses on December and January in the local channels Elite, TV Color and TV Mic, with the aim of making a comparison between the two months; where the general objective to identify which are the social representations about the older adults in the television news in Latacunga city. The methodological strategy that has been implemented in this project has a quantitative approach through the technique of observation, in the first record it has been considered to determine which are the dates, within the two months established, in what news is made about people from the third age, the same one that helped us to determine the social representations that the television news broadcasters transmit to refer to said social group. These results served as identification parameters for the second observation area, in order to help how to define the most repeated terms in the three media. Finally, the third file was intended to establish who most frequently incurred this error, where the main purpose is to identify what kind the instrument is. The contribution for this researching made to society is the understanding of the importance of the correct use of terms to refer to the elderly, especially for the means of communication to take this problem into account, as well as to warn the media, about the importance of generating spaces for the elderly and that they are not taken into account only on specific dates. In this way it has been concluded that the use of inappropriate terms in public spaces such as the news, can generate inappropriate or offensive social representations, in this case the news of the channels Elite, TV Color and TV Micc fall into this error, in addition to it They give little follow-up to the events surrounding the elderly. Being Tv color in his informative "Reporters in action" the one that more affects in this problem, while Elite, in his informative "events" does it with less frequency.